Enduring Abuse for the Sake of Remittance: The sacrifices of trafficking victims - Hamid, Haezreena Begum Abdul (Anti-Trafficking Review, 2025)
This article discusses the interrelationship between exploitative practices and financial empowerment of trafficked women. It provides a nuanced understanding of women’s motivations for migration and considers the impact of migration on victims and their families. Drawing from three months of observations and 18 qualitative interviews with female victims of trafficking in Malaysia, the article discusses women’s perception of financial empowerment and the sacrifice, pain, and suffering they endured in exchange for an exploitative income. The findings revolve around three main themes: (i) the role of domestic violence in contributing to exploitation; (ii) the need for victims to support family as a reason to migrate for work, and (iii) enduring abuse and exploitation to support family and avoid the shame of returning empty-handed. The findings highlight how women are willing to endure various forms of abuse, including exploitation, mistreatment, and harsh working conditions, to provide financial support for their families and how domestic violence often serves to facilitate or render women vulnerable to exploitation